Stakeholders satisfaction and sustainable success - Fonseca, L. (2016)
The relationship between Stakeholders Satisfaction and Organisational Sustainable Growth and Success is investigated focusing on the importance of a firm’s relationships with critical stakeholders that may lead to better performance, as organisations while integrating business and societal considerations create value for their stakeholders. However, it is of most importance that Top Management actively leads this approach and that the Governance Bodies of the Organisations support and check that this really happens. Framed on Stakeholder Theory and Social Responsibility Theory an online survey was administered to Managers of Portuguese organisations with certified management systems by a leading management Systems Certification Portuguese Body. The findings suggest that Competitive position is strongly correlated with Shareholders, Suppliers and Partners, Employees and Customers satisfaction, legitimating Freeman Stakeholder Theory. In an overall final remark, the importance of Shareholders, Partners/Suppliers, Employees and Customers satisfaction for organisational Sustainable Success is highlighted in this study results.